A Model Socialist Steel Town Enters the Neoliberal Age: The Changing Political Economy of Nowa Huta, Poland. Issue 1 (January 2015) - Pozniak, Kinga
Abstract This article examines how changing political and economic ideologies and projects—first socialism, then neoliberal capitalism—were worked out in a Polish industrial town called Nowa Huta. Nowa Huta was initially built after World War II as a town that would embody the socialist state's goals of industrialization, urbanization, and the creation of a working class. Following the collapse of the socialist government in 1989 and the ensuing market reforms, Nowa Huta experienced deindustrialization, privatization of state enterprise, unemployment, and decay of urban infrastructure. The article traces how this changing political economy was worked out in the cityscape and in the relationship between place, work, and community. It argues that the case of Nowa Huta allows us to see how global processes, such as industrialization and deindustrialization, and the changing organization of economy and work, are domesticated in local places and in relation to local politics and histories.